KINERJA PEGAWAI NEGERI SIPIL KANTOR KEMENTERIAN AGAMADI KABUPATEN SAMBAS PERSPEKTIF EKONOMI SYARIAH - Sulis Solehah; Wulan Purnamasari; Beti Yanuri Posha (Pascasarjana, Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2022)
Research is departing from the shortage of hours of work required of employees Office of Religious Affairs District Sambas and where employees are not to be in the office at the time of hours of work. Supposedly the working hours of employees is a tool to achieve employee performance targets. In addition to the employee is also difficult when asked to make the assessment of performance at the end of the year , so that the achievement of the performance of an employee is not able to note that actual. The purpose of research it is to know the performance of employees of the Ministry of Religion District Sambas, knowing the factors that support and hinder the kineja employees of the Ministry of Religion District Sambas and determine the performance of employees of the Ministry of Religion District Sambas Perspective of Economic Shariah . This study uses a qualitative approach and the type of field research . Total with the number of respondents 4 people. Mechanical collection of data using the methods of observation and interviews . The data analysis techniques used are : data collection , data reduction , data presentation and conclusion drawing .Results of the study showed that the performance of the quantity of work employees are not able to know with certainly , because the employee did not perform the determination of the target 's performance at the beginning of the year while the quality of work of employees is good , because employees work with carefully and correctly . Employee work behavior which consists of : Service orientation , integrity , commitment and Employee cooperation is good . Discipline employees kurag well especially on adherence to the presence of work . Factors that support performance are : ability to work, motivation of work and compensation that is received by an employee. Performance inhibiting factor is employee discipline. From the perspective of sharia economics, employees have shiddiq, amanah, fathanah and tabligh behavior.